Koninginins R-S from the endophytic fungus Trichoderma koningiopsis. Issue 7 (3rd April 2017) - Hu, Ming; Li, Qi-Ling; Yang, Ya-Bin; Liu, Kai; Miao, Cui-Ping; Zhao, Li-Xing; Ding, Zhong-Tao
Abstract: Two new metabolites named koninginins R-S (1 –2 ) were isolated from the culture of Trichoderma koningiopsis YIM PH30002. Their chemical structures were elucidated by the extensive spectroscopic analysis. These isolated compounds showed certain antifungal activities against phytopathogens, Fusarium flocciferum and Fusarium oxysporum . Abstract :